2010
DOI: 10.1902/jop.2010.090575
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Oral Contraceptives on Women's Periodontal Health and the Subgingival Occurrence of Aggressive Periodontopathogens and Candida Species

Abstract: OC use may increase the risk of severe periodontitis and seems to cause a selection of certain Candida species in periodontal pockets. OC users showed a higher prevalence of P. gingivalis, P. intermedia, and A. actinomycetemcomitans compared to non-users. C. albicans, C. parapsilosis, C. krusei, C. tropicalis, and C. glabrata were the species with the ability to survive in the conditions created by the sex hormones after 3 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 46 publications
(148 reference statements)
0
44
0
1
Order By: Relevance
“…Finally, A. actinomycetemcomitans has been associated with severe periodontitis [44]. In vitro, A. actinomycetemcomitans adheres to hyphae, although interactions with C. albicans show decreased fungal biofilm formation which is mediated by the luxS-synthesised autoinducer-2 (AI-2)-dependent mechanism.…”
Section: Periodontal Disease: An Uncontrolled Ganglandmentioning
confidence: 99%
“…Finally, A. actinomycetemcomitans has been associated with severe periodontitis [44]. In vitro, A. actinomycetemcomitans adheres to hyphae, although interactions with C. albicans show decreased fungal biofilm formation which is mediated by the luxS-synthesised autoinducer-2 (AI-2)-dependent mechanism.…”
Section: Periodontal Disease: An Uncontrolled Ganglandmentioning
confidence: 99%
“…Moreover, oral contraceptive users also showed a higher prevalence of P. gingivalis, P. intermedia, and A. actinomycetemcomitans as compared to non-users [16]. Brusca MI et al, (2010) The gingival index and plaque index of contraceptive users was increased as the duration of oral contraceptive increased, 23 subjects using oral contraceptives for ≤ 12 months showed mean gingival and plaque index of (1. The test group showed increased probing depth (2.228±0.011 x 2.154±0.012; p<0.0001) and sulcular bleeding index (0.229±0.006 x 0.148±0.005, p<0.0001) than controls. No significant differences between groups were found in clinical attachment level (0.435±0.01 x 0.412±0.01; p=0.11).…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Farhad SZ et al, in 2013, the significant difference in the probing pocket depth (3.78) and clinical attachment loss (1.87) was found between the case and control groups (p<0.05) [16]. According to the study conducted by Brusca MI et al, in 2010 it was found that the oral contraceptive users had deeper probing depths (≥5 mm) than non-users and clinical attachment loss ≥5 mm than non-users (p<0.01) [15]. In a study by Ardakani AH et al, in 2010 he found mean pocket depth and attachment loss of oral contraceptive user and non oral contraceptive user are 2.06 ± 0.22, 2.1 ± 0.20 and 1.0004 ± 0.23 and 0.98 ± 0.24 respectively [13].…”
Section: Effects Of Interventionmentioning
confidence: 99%
“…A PCR assay optimization was performed with specific primers derived from sequences of the ITS1-5.8SrRNA-ITS2 region (Table 1), according to a study conducted by Asadzadeh et al [30]. The results were validated using Sanger sequencing, for which we employed an end-point PCR with ITS 1 and ITS 4 panfungal primers to amplify and sequence the ITS 1-ITS 4 region of the 28S ribosomal RNA gene, as described by White et al [21]. Amplified fragments were purified using the QIAquick PCR Purification Kit (Qiagen) and sequenced using the ABI Prism 3730XL DNA Analyzer (Applied Biosystems, Bs.As.-Argentina), with primers ITS 1 and ITS 4.…”
Section: Species Identificationmentioning
confidence: 99%
“…15. subjects. Among the local and/or systemic factors associated with the higher distribution of NAC species in the oral cavity, we could mention the use of prosthetic devices [11]; being elderly, [15] elderly with low body mass index [16]; being an oncological patient undergoing chemotherapy or radiotherapy [17,18]; being a diabetic patient with poor metabolic control [19], being a man using anabolic androgenic steroids [20] or a woman using oral contraceptives [21].…”
Section: Introductionmentioning
confidence: 99%